Amostragem da emissão de material particulado em ambientes externos - Lima, Bruno de Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The concern of the society with regard to the pollution if becomes each bigger and necessary time. This pollution generates damage for who is in contact, as much in economic terms how much in quality of life. The particulate matter is one of the main polluting the air, being the most harmful to human health, fine particles and ultra fine (below 2.5 μm in diameter). With this, this work had as objective to mensurar the pollution of air for material particulado through samplings in an urban center, in a siderurgical industry, a conventional coal bunker and a forest fire. The equipment used for the sampling of particles had been the DataRam4 (model DR 4000) and the Impactador de Andersen, both developed by company THERMO SCIENTIFIC. The first equipment uses a system of nefelometry and the second uses a gravimetrical system of sampling. During the carried through samplings, it can be observed in some cases the difficulty in the breath, badly be and low visibility that this type of pollutant can cause. In most cases the results were disturbing. In industry, conventional coal bunker and in the forest were measured values high concentration for particles smaller diameters. Peak concentrations issued were: 40,000 μg/m³, 182,000 μg/m³ and 400,000 μg/m³ for the industry, conventional coal bunker and forest, respectively. Already in the urban centre were satisfactory results, always staying within the limit allowed by the rules in force so far in the country
Keywords: Ar - Poluição - Medição; Ar - Qualidade; Aparelhamento para amostragem do ar; Ar - Analise; Air - Pollution - Measurement